Application of Picosecond Laser in Dermatology - Bintanjoyo, Lunardi; Indramaya, Diah Mira (Faculty of Medicine, Universitas Airlangga, 2023)
ABSTRACT Background: Lasers are one of the most important treatment modalities in dermatology. Lasers interact with chromophores through several mechanisms that depend on fluence and pulse durations. Early lasers worked by photothermal interaction with pulse durations of 1 microsecond to 1 second. A picosecond laser is developed to confine photothermal effects and produce photomechanical effects and plasma induction. Purpose: To understand the mechanism of action and application of picosecond lasers for dermatological disorders. Review: Non-fractional picosecond lasers work by photomechanical interaction. Photomechanical interaction happens when pulse duration is less than inertial confinement time, causing fractures of chromophores with lower energy, or